Associations between movement synchrony and outcome in patients with social anxiety disorder: Evidence for treatment specific effects. (3rd July 2020) - Altmann, Uwe; Schoenherr, Désirée; Paulick, Jane; Deisenhofer, Anne-Katharina; Schwartz, Brian; Rubel, Julian A.; Stangier, Ulrich; Lutz, Wolfgang; Strauss, Bernhard
ABSTRACT: Background : Studies with heterogeneous samples in naturalistic treatment settings suggest that movement synchrony (MS) between therapists and patients correlates with therapeutic success. In this study, we examined a homogeneous sample of patients with social anxiety disorder and investigated whether MS in sessions 3 and 8 would be associated with therapy outcome and therapeutic alliance, and whether these associations depend on the therapeutic approach. Methods : The patients ( N = 267) were treated with either manual-guided cognitive behavior therapy (CBT), manual-guided psychodynamic therapy (PDT), or naturalistic CBT. The Helping Alliance Questionnaire (HAQ), the Inventory of Interpersonal Problems (IIP) and the Beck-Depression-Inventory (BDI) were used as measures. Body motions were coded with motion energy analysis. MS was quantified using time series analysis methods. Results : MS was observed more frequently in both CBT conditions than in PDT. In both CBT groups, more synchrony was predictive of lower IIP scores at the end of therapy. If the patient lead synchrony more often than the therapist, higher IIP and BDI scores were observed at the end of treatment. PDT showed the largest effect size for the synchrony-alliance-association. Conclusion : Movement synchrony and therapeutic success are associated. The effect of therapeutic approach and leading/following are relevant for this association.